Do uso à mediação de tecnologias no ensino-aprendizagem de ciências: uma abordagem investigativa de prática educacional no ensino fundamental - Darronqui, Silvia Regina (2013)
This thesis presents a theoretical and practical approach about the mediation of technology in teaching and learning of Natural Sciences. This case study was developed with students from four classes ninth year of the Public Elementary School Teacher's Victor Amaral, located in Curitiba – PR. The main objective of this research was to investigate whether the questioning of technologies may provide for the construction of a knowledge for differentiated teaching and learning of Natural Sciences in Elementary Education. It is understood that differentiated knowledge that goes beyond that provided in the curriculum, which is critical, reflexive and contextualized. This qualitative action research followed the stages: application of the initial questionnaire, which proved the necessity of the existence of this research, conducting classes in Physics (Science) with the application of the questionable methodology of Freire through didactic sequences theoretically grounded and a questionnaire end. The technologies were present in the classroom as a teaching resource and learning content aimed collaborate to make students active, critical and reflective in relation to content and technology worked. The methodology used in the teaching sequences and therefore in the classroom, was problematical, containing the three pedagogical moments: problematization, organization and application of knowledge. This research was based on authors such as Freire, Vicente, Pacey, Postman and Bazzo, among others. Based on "the importance of the act of reading" Freire (1989) became a transposition to the necessary reading technologies, which were created guiding principles of the work. This theoretical reflection was needed to support the thinking that the didactic sequences aimed at providing the students. Data collection occurred through initial and final questionnaire for field diary and transcripts of audio-recorded lessons. The results showed that problematize technology in education provides a differentiated knowledge acquisition. We conclude that education mediated over/with technology contributes to learning, favoring a more effective participation by providing discussion and reflection among students, thus boosting science education.